Social Media and Mental Health: (A Comprehensive Examination of Depression, Anxiety, and Body Image Concerns) - Dr. Yaser A. Alghamdi (Journal of Arts, Literature, Humanities and Social Sciences, 2024)
The growing prevalence of media in our lives has sparked discussions among experts about its effects on well-being, especially among vulnerable groups such as young adults and women. Individuals with these demographic characteristics are more prone to mental health issues due to factors such as interpersonal comparison and cyberbullying. In this study, a segmented approach was adopted to examine the connection between media utilization and its influence on psychological health such as depression, anxiety and body image concerns. Using structured questionnaires, data was collect from a sample of 611 Saudi Arabian residents aged 18 and above. Statistical analyses, including Chi-square, correlation and path analysis, were conducted to examine these associations. Results revealed concerning patterns, with 30.6% of participants reporting heightened symptoms of depression. Females exhibited higher rates (35.02%) in comparison to males (22.48%). Anxiety symptoms presented in 66% of the sample group. Additionally, more than 40% of social media users expressed concerns about their body image. Age was found to have a moderating effect on the association between social media usage and anxiety levels, indicating a stronger impact on anxiety symptoms among older individuals compared to younger individuals, while gender did not appear to have any influence. These findings hold implications for public health policies and interventions underscoring the importance of tailored programs that address the health risks associated with social media use. To shape policies, it is important to focus on advancing literacy by implementing awareness programs and creating preventive measures specifically designed for vulnerable groups.